Hydration status and perception of fluid loss in male and female university Rugby Union players - Muth, T.; Pritchett, R. C.; Pritchett, K.; DePaepe, J.; Blank, R. (International Journal of Exercise Science, 2019)
Rugby union players are at risk for dehydration due to the high physiologic demand of the sport (~7.5 MJ/game). Dehydration could be due to lack of knowledge of fluid lost during activity. Therefore, the purpose of this study was to observe the hydration status and sweat loss estimations of male and female university rugby union players over three consecutive training sessions. Body mass, urine specific gravity (USG), and self-reported thirst scores were recorded pre and post training sessions. Sweat loss estimations were recorded post training session. After estimations, participants were shown his or her actual sweat loss in hopes of improving estimations over the three sessions. Paired t-tests were used to determine significance between pre and post training USG, thirst level and body mass for each day. A general linear mixed-effect model was used to determine significance of the difference between variables within gender and within days. Mean body mass changes did not exceed 2% lost for either gender on any of the three training sessions. Males significantly underestimated sweat loss by ~81% (p<0.01) after session one and improved estimations to ~36% after session three, however still significantly underestimated (p<0.01). Females also significantly underestimated sweat loss by ~64% on day one (p<0.01), and also improved estimations to ~60% on day three, however, still significantly underestimated (p<0.01). Results indicate that, on average, the participants remained in a euhydrated state throughout the training sessions. Findings also show that through education participants can improve perceptions of sweat loss to remain in euhydrated state.